Preparation of starch from breadfruit (Artocarpus altilis) with dual modification through oxidation and cross-linking methods - Cut Fatimah Zuhra; M Zulham Efendi Sinaga; Suharman; Petra Josua Situmorang (Applied Food Research)
The synthesis of dual-modified starch through sequential oxidation and cross-linking reactions has been successfully carried out. The dialdehyde starch was derived from breadfruit (Artocarpus altilis) starch modified through oxidation with sodium periodate and then modified by crosslinking using trisodium trimethaphosphate and citric acid as catalysts, which were then compared to determine the most effective catalyst. The formation of dialdehyde starch was confirmed by FT-IR spectra, at 1736.9 cm-1 a characteristic peak appeared indicating the vibration of the carbonyl aldehyde group so that the resulting functional group did not have excessive functional groups so that it was not problematic with food regulations. The optimal oxidation degree (81 %) was achieved using sodium periodate. SEM analysis of the modified starch showed fine and granular morphological features. In addition, these starches showed favorable thermal and physicochemical changes, with reduced swelling power and solubility. As a result, modified starch was obtained with a good degree of substitution with trisodium triphosphate modified starch value of 0.019 and citric acid modified starch value of 2.080 as the best degree of substitution values. Thus, these modifications offer potential applications for the advancement of starch-based materials with better functionality in various industries.